História da Saúde Mental infantil: A criança Brasileira da Colônia à República Velha - Ribeiro, Paulo Rennes Marçal [UNESP] (My University, 2006)
This paper proposes a reflection on Child Mental Health in Brazil and describes the process of constitution and development of medical, psychological and psychiatric care to children from Colony to Old Republic. In the colonial period there are reports and documents written by voyagers. In the 18th century a new concept of childhood was developed and in the 19th century the main concern about infancy was mortality and family care.
History of childhood mental health: Brazilian child from Colony to Old Republic
Keywords: Childhood; History of childhood; Mental health